Analysis Compound Word in Harry Potter and The Philoso-pher’s Stone - Ni Kadek Linda Wati; Ida Ayu Mela Tustiawati (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2026)
This study examines the types of compound word constructions and their elements found in the novel Harry Potter and the Philosopher's Stone. The research is based on Katamba’s (2015) theory of compound words. A qualitative approach is employed to analyze the compound words present in the novel. Data collection involved several techniques, including downloading the novel text, reading it to understand the content, and coding compound words. The analysis focuses on identifying, classifying, and interpreting these compound words to explore their contribution to the narrative. This study also investigates the role of compound words in enhancing the meaning and linguistic texture of the novel. It reveals how compound words form an integral part of the story’s structure and character development, showing their significance in both everyday language use and literary construction. The findings provide a deeper understanding of how compound words function within the text and highlight their impact on readers' perception and engagement with the story. Overall, this research demonstrates the importance of compound words in language construction and narrative development, offering valuable insights into their use in literary works.